Panchayats and women self help groups: understanding the symbiosis - Salgaonkar, Seema; Salgaonkar, Pradeep B. (2009)
Empowerment of women emphasizes on creation of environment which promotes equality between women and men. The state has, through it policies, planning and schemes, tried to create this environment. The National Perspective Plan for Women (1988) emphasized on two aspects, the economic development and integration of women into the mainstream of our economy, and equity and social justice to all women. The more recent efforts of the state in this direction has been dual, provision of thirty-three percent reservation for women in Panchayat Raj Institutions and promotion of micro credit scheme of Women Self Help Groups (WSHGs). Both these measures possessing independent capacities of bringing in positive change, if synergized can bring in silent revolution at grassroots. - Reproduced.
Keywords: Self help; Women; Panchayat